2017
DOI: 10.2147/ott.s135664
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-148b suppresses proliferation, migration, and invasion of nasopharyngeal carcinoma cells by targeting metastasis-associated gene 2

Abstract: PurposeMicroRNAs (miRNAs) play important roles in tumorigenesis and metastasis by regulating genes expression. MiRNA-148b (miR-148b) had been reported to inhibit tumor progression in some kinds of cancers, but the functions of miR-148b in nasopharyngeal carcinoma (NPC) remain largely unknown. The aim of this study was to investigate the functional role of miR-148b in NPC.MethodsExpression of miR-148b in NPC tissues and cell lines was detected by quantitative reverse transcription polymerase chain reaction. MiR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Further investigations are needed to reveal their functions and mechanisms in NPC tumorigenesis. Some of the NPC-related miRNAs found in previous studies were not identified in this study, including targeting of STAT3 by miRNA-98, targeting of TGF β R2 by miR-93, and targeting of metastasis-associated gene 2 by miRNA-148b [ 44 46 ]. These partially inconsistent results may reflect differences in sample types, screening tools, or quantification methods.…”
Section: Discussionmentioning
confidence: 70%
“…Further investigations are needed to reveal their functions and mechanisms in NPC tumorigenesis. Some of the NPC-related miRNAs found in previous studies were not identified in this study, including targeting of STAT3 by miRNA-98, targeting of TGF β R2 by miR-93, and targeting of metastasis-associated gene 2 by miRNA-148b [ 44 46 ]. These partially inconsistent results may reflect differences in sample types, screening tools, or quantification methods.…”
Section: Discussionmentioning
confidence: 70%
“…Several miRNAs have been reported to serve as oncogenes or suppressor genes in NPC cell migration, invasion and metastasis. These miRNAs include miR-145 [8], miR-429 [9], miR-143 [10] and miR-148-b [11]. These studies suggest that miRNAs play important roles in NPC and provide a novel area of study in NPC invasion and metastasis.…”
Section: Introductionmentioning
confidence: 83%
“…Excessive migration and invasion of tumor cells is recognized as the first step of neoplasm metastasis. 19 , 20 The effect of decreased Nodal expression on cell migration and invasion was determined by transwell assay. Our results demonstrated that downregulation of Nodal significantly inhibited the cell migration and invasion capabilities of bladder cancer cells.…”
Section: Discussionmentioning
confidence: 99%